2022
DOI: 10.1101/2022.10.24.513511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cholinergic Modulation Shifts the Response of CA1 Pyramidal Cells to Depolarizing Ramps via TRPM4 Channels with Potential Implications for Place Field Firing

Abstract: A synergistic combination of in vitro electrophysiology and multicompartmental modeling of rat CA1 pyramidal neurons identified TRPM4 channels as major drivers of cholinergic modulation of the firing rate during a triangular current ramp, which emulates the elevation in synaptic input received while traversing the place field. In control, fewer spikes at lower frequencies are elicited on the down-ramp compared to the up-ramp. The cholinergic agonist carbachol (CCh) reverses this spike rate adaptation, causing … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 142 publications
0
1
0
Order By: Relevance
“…Another putative substrate for persistent activity relies on the intrinsic bistable dynamic of individual neurons (Zylberberg and Strowbridge 2017). On the single cell level, persistent Na + current (Yamada-Hanff and Bean 2013) in CA1 pyramidal cells, Ca 2+ activated Ca 2+ currents in entorhinal cortical pyramidal cells (Egorov et al 2002) and CA1 pyramidal cells (Combe et al 2023), and low threshold Ca 2+ currents in other cells (Otsuka et al 2001;Perrier et al 2002) have been shown to contribute to regenerative firing, by making the neuron bistable or even multi-stable, and thus more likely to continue firing after excitation is terminated.…”
Section: Introductionmentioning
confidence: 99%
“…Another putative substrate for persistent activity relies on the intrinsic bistable dynamic of individual neurons (Zylberberg and Strowbridge 2017). On the single cell level, persistent Na + current (Yamada-Hanff and Bean 2013) in CA1 pyramidal cells, Ca 2+ activated Ca 2+ currents in entorhinal cortical pyramidal cells (Egorov et al 2002) and CA1 pyramidal cells (Combe et al 2023), and low threshold Ca 2+ currents in other cells (Otsuka et al 2001;Perrier et al 2002) have been shown to contribute to regenerative firing, by making the neuron bistable or even multi-stable, and thus more likely to continue firing after excitation is terminated.…”
Section: Introductionmentioning
confidence: 99%